Time out of joint - Dick, Philip K. (New York : Vintage Books, 2002)
After a series of troubling hallucinations, Ragle Gumm begins to suspect that his memories have been altered and that he is living in a universe gone terribly awry.
Originally published: New York: J.B. Lippencott, 1959.
Adult.
Adult
Keywords: Puzzles -- Psychological aspects -- Fiction; Space and time -- Fiction; Suburban life -- Fiction; Psychological fiction; Puzzles -- Psychological aspects -- Fiction; Science fiction; Space and time -- Fiction; Suburban life -- Fiction; Psychological fiction; Science fiction